The Efficacy of Juvenile Court Supervision in Addressing Youth Risks and Needs - Rapanos, Ashtaan (Journal of contemporary criminal justice, 2025)
We examine the efficacy of juvenile supervision practices by testing whether significant reductions in criminogenic risk/need, as measured by the Youth Level of Service/Case Management Inventory (YLS/CMI) in official juvenile court data, occur between court entry and exit. Furthermore, we test whether the effectiveness of court interventions differs by demographic and offense-related factors. The findings reveal that although risk decreases significantly while under court supervision, that risk reduction is attenuated for Black male youth (compared to white males), youth placed in multiple programs (compared to those placed on probation or a single court-ordered intervention), and youth under court supervision for a longer duration. These findings emphasize the importance of implementing culturally informed, individualized treatment planning within the juvenile justice system.